489Trends in method-specific suicide among Japanese adolescents in the past four decades. (2nd September 2021) - Dhungel, Bibha; Thapa, Anushka; Martinez-rives, Noelia Lucia; Martin, Pilar; Wada, Koji; Gilmour, Stuart
Abstract: Background: In 2018 the overall suicide rate increased by 33% among students, as a part of a continued trend of rising suicide among adolescents. In 2015, the government of Japan aimed to reduce the overall suicide rate to 13 per 100, 000 or less by 2025, but deaths among adolescents have been rising. This study analysed the trends in method-specific suicide among Japanese adolescents from 1979 to 2016 and compared suicide mortality rate in Japan with other OECD countries. Methods: We obtained vital statistics data from the Japanese Ministry of Health, Labour and Welfare as well as the global health observatory of the WHO. Poisson regression analysis was performed separately by sex with year, age category, suicide method and a 1998 step variable as covariates. Results: We found that hanging suicide rates among high school level boys are 12.15 times and girls are 6.17 times the rate of elementary school-aged children. The year 1998 saw a peak in suicide rates by hanging, which increased by more than 60% among both boys and girls. Japan is near the median of OECD suicide rates, with crude suicide mortality rates of 7.8 per 100, 000 among 15–19-year-olds in 2016. Conclusions: Suicide among adolescents has been rising during the last decades. Several factors related to the school and family environment, and mental health problems may have affected the adolescent suicide rate in Japan Key messages: An urgent need is evident to address suicide among high school and university-aged adolescents.